2015
DOI: 10.1007/s00382-015-2841-5
|View full text |Cite
|
Sign up to set email alerts
|

Global monsoon change during the Last Glacial Maximum: a multi-model study

Abstract: resulting in a general weakening of the GM precipitation and reduction of GM domain. The reduced hemispheric difference in seasonal variation of insolation may contribute to the weakened GM intensity. The changed land-ocean configuration in the vicinity of the Maritime Continent, along with the presence of the ice sheets and lower greenhouse gas concentration, result in strengthened land-ocean and North-South hemispheric thermal contrasts, leading to the unique strengthened Australian monsoon. Although some of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 45 publications
5
26
0
Order By: Relevance
“…Global paleoclimate models in SWIO and East Africa also suggested variations in the rainfall pattern and a dryer period surrounding the LGM. Using multimodel ensemble, Yan et al (2016) showed a reduction of the monsoon domain as well as in monsoon intensity regarding southern Africa during the LGM. The LGM period was also associated with rainfall variations in equatorial East Africa, but the peak glacial drought overlapped only partly with the LGM proper (Gasse et al, 2008;Verschuren et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global paleoclimate models in SWIO and East Africa also suggested variations in the rainfall pattern and a dryer period surrounding the LGM. Using multimodel ensemble, Yan et al (2016) showed a reduction of the monsoon domain as well as in monsoon intensity regarding southern Africa during the LGM. The LGM period was also associated with rainfall variations in equatorial East Africa, but the peak glacial drought overlapped only partly with the LGM proper (Gasse et al, 2008;Verschuren et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…1b). Regarding the LGM, global paleoclimate modelling predicted that a reduction in temperature (from À1°C to À3°C, Barrows & Juggins, 2005;Otto-Bliesner et al, 2009;Weigelt et al, 2016) and a reduction in rainfall (À10% according to Yan et al, 2016) are likely to have occurred at regional scale in the SWIO. The impact of past climatic events on the demographic history of native species and their paleodistribution remains understudied in Reunion Island.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the proxy records, model simulations capture the changes in tropical mean state (Braconnot et al 2007a, b;Deckker et al 2002;Mohtadi et al 2011Mohtadi et al , 2017Kageyama et al 2013;DiNezio1 and Tinerney 2013;Brady et al 2013;Niedermeyer et al 2014), the Northern westerlies (Oster et al 2015;Wang et al 2018), the Northern Hemisphere (NH) ice sheet-related precipitation (Luetscher et al 2015;Oster et al 2015), and the Southern westerlies (Heusser 1989;Rojas et al 2009;Sime et al 2013). Extensive studies have been conducted to explain changes in the Intertropical Convergence Zone (ITCZ) (Donohoe et al 2013;Mcgee et al 2014;Braconnot et al 2007b), global and regional monsoon activities (Braconnot et al 2000;Jiang and Lang 2010;Yan et al 2016Yan et al , 2018, NH jet stream (Laîné et al 2009b;Hofer et al 2012;Oster et al 2015), El Niño-Southern Oscillation (ENSO) variability (Ford et al 2015), hydrological sensitivity (Li et al 2013;Harrison et al 2015) and climate sensitivity (Schmittner et al 2011;Annan and Hargreaves 2013;Hopcroft and Valdes 2015). Change of greenhouse gas (GHG) concentrations and existence of land ice sheet, along with the associated sea level drop and exposure of the continental shelf, have been generally recognized as the main drivers of the LGM climate formation.…”
Section: Introductionmentioning
confidence: 89%
“…Single forcing experiment with coupled climate models is advantageous for assessing the relative contributions of each forcing to global climate change, which includes changes in the mean states of precipitation and temperature, global monsoon, ITCZ and ENSO. For example, Yan et al (2016Yan et al ( , 2018 found that the Australian monsoon, in contrast to all other regional monsoons, is strengthened and expanded during the LGM. This unique feature cannot be qualitatively explained by a full forcing experiment or the GHG forcing alone.…”
Section: Introductionmentioning
confidence: 99%
“…This means that CAM4 has a global range of 48 grid points in latitude, 96 grid points in longitude, and 26 vertical levels, while POP2 has 116 grid points in latitude, 100 grid points in longitude, and 60 vertical levels. The CESM is the one of the main models cited in the Fifth Assessment Report of the Intergovernmental Panel on Climate Change and the performance of CESM has been verified by many researchers Ning and Bradley 2016;Otto-Bliesner et al 2016;Yan et al 2016). CESM is used to simulate a long-time integration, including a control experiment (Ctrl) and a volcanic sensitivity experiment (Vol).…”
Section: Model and Experimentsmentioning
confidence: 99%